ANALISIS STRATEGI PENGARUH PENERAPAN DIMENSI SALES PROMOTION TERHADAP KEPUTUSAN PEMBELIAN DI EVERY TOUR & TRAVEL - Veren Charlotta; Hari Iskandar (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Every Tour & Travel is a small-scale travel agent and will only enter the world of travel in 2021. Every Tour & Travel is the brand name of PT. Young Indonesian Explorers which is the name of the company. Every Tour & Travel provides travel package products, prices, travel plans, travel consultants, and others related to travel activities. This research was conducted with the aim of knowing the Sales Promotion factors that influence purchasing decisions at Every Tour & Travel. In this study, researchers used descriptive analysis with quantitative methods and took samples using a purposive sampling approach with the Slovin formula so the total customer population at Every Tour & Travel every month from 2021 to 2022. The data collection technique was carried out by distributing questionnaires to 100 respondents who have made transactions and have seen Sales Promotion media on Every Tour & Travel. For data analysis techniques, researchers used descriptive analysis of respondents and variables, validity test, reliability test, t test, F test, Coefficient of Determination (R2), Simple Linear Regression TEST, Normality test, and Heteroscedasticity test using the SPSS 25 program. Based on the results of research conducted using the t test, the results show that Sales Promotion (X) has a partial effect on the Purchase Decision variable (Y). The results of research conducted using the F test, the results show that the Sales Promotion variable (X) has a simultaneous effect on the Purchase Decision variable (Y). The test results for the Coefficient of Determination (R2) based on this study show that the R2 value is 0.852 or 85.2% which indicates the level of influence of the Sales Promotion (X) variable on the Purchase Decision variable (Y), so it can be said that 14.8% is influenced by other variables outside the research. The results of the Simple Linear Regression test show that the Purchase Decision variable (Y) can be influenced by Sales Promotion (X). The conclusion from the results of this study is that Sales Promotion has a partial effect on the Purchasing Decision variable either partially or simultaneously.